PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL ( Studi Pada Badan Pemberdayaan Perempuan dan Keluarga Berencana Kabupaten Pati ) - Pangestu, Widiyati; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2015)
Problems in BPPKB that employees are not promoted and promotion is not done based on the performance showed that job satisfaction is less than optimal, structural pejabatan appointed instead of PP and KB Agency showed less than optimal competency, career development is less than optimal because of promotions are not transparent and commitment organizational less than optimal due to employees who move to other agencies. This study aimed to determine the effect of competence and career development to job satisfaction and organizational commitment mediation studies of Women Empowerment and Family Planning Pati regency. The population is an employee in the District BPPKB much as 137 people. Sampling techniques using the census was taken of all as a population of 137 employees. The statistical techniques used are validity with components of the matrix, Cronbach alpha reliability test, multiple regression analysis, t test and r2 with an adjusted R-square. The results reveal that the competence has possitive and significant effect on job satisfaction ( beta 0,294 sig = 0.000 ) . Career development has positive and significant effect on job satisfaction ( beta 0,366 sig = 0.000 ) . Organizational commitment has possitive and significant effect on job satisfaction ( beta 0,317 sig = 0.000 ) . Career development has possitive and significant effect on organizational commitment ( beta 0,249 sig = 0,000 ) . Competence has possitive and significant effect on organizational commitment ( beta 0,585 sig = 0.000 ) . Organizational commitment mediate the effect of competence on the job satisfaction of employees. Organizational commitment mediate the effect of development on job satisfaction career.Keywords: Competence, career development, job satisfaction and organizational commitment